New carnivorous sponges and allied species from the Great Australian Bight - Ekins, Merrick; Erpenbeck, Dirk; Goudie, Lisa; Hooper, John N.a. (Zootaxa, 2020)
This research presents three new species of carnivorous sponges from the family Cladorhizidae from the Great Australian Bight, South Australia. This research also shows a clear separation within the species currently known as Cladorhiza into those with an arbuscular or tree-like morphology from the Atlantic, to those of differing morphologies and propose three new genera, i.e. Bathytentacular gen. nov., Abyssosdiskos gen. nov. and Nullarbora gen. nov. and the resurrection of an old genus Axoniderma. nov. The three new species described in this paper are Nullarbora heptaxia sp. nov., Abyssocladia oxyasters sp. nov. and Lycopodina hystrix sp. nov. A new species in the family Guitarridae, Guitarra davidconryi sp. nov., a family closely related to the carnivorous sponges is also described in this paper. These new species are the first recorded carnivorous species from South Australia and increase the number of species recorded from around Australia to 25.